Characterisation Of Sheet Resistivity And Contact Resistivity For Source/Drain Of N-Mosfet Device - Rhonira, Latif (Penerbit Universiti, UTeM, 2014)
In this study, the sheet resistivity (ps) of the thin film phosphorus ion source/drain implantation regions, and the specific interfacial contact resistivity (pc) between the thin film aluminium 1% silicon electrode layer and the thin film phosphorus ion source/drain implantation regions of the n-channel metal-oxide-semiconductor field effect transistor (n-MOSFET) devices have been characterised using the Greek cross and Kelvin resistor test structures. From TSUPREM-4, the dose and energy of the phosphorus ion beam have been simulated to influence the sheet resistivity of the source/drain implantation regions. The secondary ion mass spectrometry (SIMS) measurement has verified the simulated surface concentration of the phosphorus ions. The measurements from the test structures have shown that the sheet resistivity and the specific interfacial contact resistivity of the source/drain terminals varied across the wafer. The influence of the heart size from the Greek cross structure and the contact area size from the Kelvin resistor structure have been investigated. In our application, the phosphorus ion dose of 1e16 ions/cm2 and energy of 40 keV have been measured to provide the desired small sheet resistivity of ps = 25.93 Ω/□. From the measured interfacial contact resistivity of pc∼10∼-4 Ωcm2, the interfacial contact area for the source/drain regions have been designed to be approximately 80 μm × 40 μm in order to achieve the reasonable interfacial contact resistance of Rc = 3 Ω. The fabrication design for the source/drain of the n-MOSFET devices is optimised in order to obtain good drain current conduction with small resistances.